We come for good : archaeology and tribal historic preservation at the Seminole Tribe of Florida - Backhouse, Paul N. (Paul Nathan); Weisman, Brent Richards, 1952-; Rosebrough, Mary Beth (University Press of Florida, 2017)
This volume offers guidance on how traditional scholars can and should integrate the work of Tribal Historic Preservation Offices (THPOs) into archaeological research by focusing on the work of the Seminole THPO.